2010
DOI: 10.1021/ja105044s
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Accelerated C−H Activation Reactions: Evidence for a Switch of Mechanism

Abstract: Initial rate studies have revealed dramatic acceleration in aerobic Pd(II)-catalyzed C–H olefination reactions of phenylacetic acids when mono-N-protected amino acids are used as ligands. In light of these findings, systematic ligand tuning was undertaken, which has resulted in drastic improvements in substrate scope, reaction rate, and catalyst turnover. We present evidence from intermolecular competition studies and kinetic isotope effect experiments that implies that the observed rate increases are a result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
242
0
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(271 citation statements)
references
References 189 publications
16
242
0
13
Order By: Relevance
“…Further screening revealed that the addition of a catalytic amount of N-9-fluorenylmethoxycarbonyl (Fmoc)-protected amino acid (20 mol%) led to a dramatic increase in the conversion of 1a to the desired product 3aa. This result was consistent with the results reported by Yu for a related reaction, 34) with valine providing the best result of all of the amino acids tested in the current study (Table 2, entries 5-9). The nature of the protecting group on the nitrogen atom of the amino acid was also found to be very important.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Further screening revealed that the addition of a catalytic amount of N-9-fluorenylmethoxycarbonyl (Fmoc)-protected amino acid (20 mol%) led to a dramatic increase in the conversion of 1a to the desired product 3aa. This result was consistent with the results reported by Yu for a related reaction, 34) with valine providing the best result of all of the amino acids tested in the current study (Table 2, entries 5-9). The nature of the protecting group on the nitrogen atom of the amino acid was also found to be very important.…”
supporting
confidence: 93%
“…Although the use of a formyl or acetyl (Ac) group did not lead to an improvement in the conversion of 1a (Table 2, entries 10, 11), the use of a carbamate protecting group such as a t-butyloxycarbonyl (Boc), methoxycarbonyl or (−)-menthyloxycarbonyl (Men) group led to an increase in the conversion (Table 2, entries [12][13][14]. In contrast to previous reports from the literature, 34) the use of a smaller charge of (−)-Men-Val-OH (5 mol%) led to an increase in the conversion of 1a (Table 2, entry 15). After fine tuning the conditions for this reaction, we established that the use of 2.0 eq of Ag 2 CO 3 with 1.5 eq of BQ led to the complete conversion of 1a, with benzocyclobutene 3aa being isolated in 84% yield after silica gel column chromatography ( Table 2, entry 16).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…However, in these cases, the mechanism should include Pd(0)/Pd(II) reoxidation of the catalyst, but not high-valent palladium intermediates [89][90][91]. However, as can be seen from the diagram in Figure 1, the oxidative strength of oxygen may not be enough to oxidize Pd(0) under certain conditions (the potential ranges of Pd(0) oxidation and O 2 reduction overlap insignificantly, at about −0.5 V).…”
Section: Methodsmentioning
confidence: 99%
“…[81] In diesem Beispiel wurde ohne Liganden nahezu keine Selektivität beobachtet; eine erste mechanistische Untersuchung sowie eine Optimierung der ursprünglichen Bedingungen wurden kürzlich veröffentlicht. [82] Darüber hinaus sind auch viele schöne Beispiele zur Aktivierung von C(sp 2 )-H-und C(sp 3 )-H-Bindungen in heterocyclischen Substraten bekannt. Zu diesem Thema ist vor kurzem ein Übersichtsartikel erschienen.…”
Section: -Zentrenunclassified